MID-REGIONAL PRO-ADRENOMEDULLIN (MR-proADM) AS A DIAGNOSTIC AND PROGNOSTIC BIOMARKER IN EARLY SEPSIS: A NARRATIVE REVIEW - Julia Świechowska; Sonia Mojzyk; Magdalena Wiciak; Ingrid Samberger; Julia Maria Kuczkowska; Zuzanna Zarzycka; Donata Pokorska; Zuzanna Michalska; Judyta Bordakiewicz; Agnieszka Morawa (International Journal of Innovative Technologies in Social Science, 2026)
Sepsis is a critical medical condition resulting from an inappropriate host response to infection, often leading to organ dysfunction and high mortality. Early diagnosis remains a significant clinical challenge due to the nonspecific nature of initial symptoms and the limited efficacy of conventional biomarkers. Commonly used markers, such as C-reactive protein (CRP) and procalcitonin (PCT), provide useful information on inflammation and bacterial infections but do not adequately reflect vascular dysfunction or predict clinical deterioration. Mid-regional proadrenomedullin (MR-proADM) has recently gained importance as a biomarker reflecting both inflammatory processes and impaired vascular integrity. As a stable fragment of proadrenomedullin, it indirectly represents the activity of adrenomedullin, a peptide involved in maintaining endothelial function and circulatory homeostasis. Evidence from observational studies indicates that MR-proADM levels increase early in the course of infection and correlate with disease progression, organ failure, and risk of death. Compared to traditional biomarkers, MR-proADM appears to offer better prognostic performance, particularly in identifying patients at risk of severe complications. Its association with endothelial damage and microcirculatory dysfunction makes it particularly relevant to the pathophysiology of sepsis. In summary, MR-proADM may be a valuable complement to existing diagnostic tools, aiding early risk stratification and clinical decision-making. Further studies are needed to standardize its use and confirm its role in routine practice.